2017
DOI: 10.1007/s11999-017-5442-2
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Risk Factors and Complications Associated With Intraoperative and Postoperative Fractures in Total Wrist Arthroplasty?

Abstract: Background Total wrist arthroplasty (TWA) can relieve pain and preserve some wrist motion in patients with advanced wrist arthritis. However, few studies have evaluated the risks and outcomes associated with periprosthetic fractures around TWAs. Questions/purposes (1) What is the risk of intraoperative and postoperative fractures after TWAs? (2) What factors are associated with increased risk of intraoperative and postoperative fracture after TWAs? (3) What is the fracture-free and revision-free survivorship o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…The current study by Gil and colleagues showed a reasonable survivorship of 77.7% at 15 years, which is consistent with other comparable recent studies that show an improved survivorship of the latest generation of implants [1][2][3][5][6][7][8]. Perhaps if this pattern of finding increased longevity and minimal complications continues to be reported, the data will serve as a counterclaim for the many steadfast skeptics.…”
supporting
confidence: 91%
“…The current study by Gil and colleagues showed a reasonable survivorship of 77.7% at 15 years, which is consistent with other comparable recent studies that show an improved survivorship of the latest generation of implants [1][2][3][5][6][7][8]. Perhaps if this pattern of finding increased longevity and minimal complications continues to be reported, the data will serve as a counterclaim for the many steadfast skeptics.…”
supporting
confidence: 91%
“…In the literature, there are no evident scientific data with the use of all third generation TWA types (including the Maestro TM Total Wrist/WRS!) that support the necessity of cementation at time of its primary insertion (Figure 1A-C, Figure 5A-B, Figure 11A-E), cementation is only recommended primarily in patients with poor bone stock (rheumatoid arthritis, advanced stage of osteoporosis) (Figure 2A-B, Figure 7) or in cases of revision TWA, and cementation does not decrease the risk of intraor postoperative periprosthetic fracture [2][3][4][5][6][7][8][9][10][11][12][13]16,17,[59][60][61][62][63]. Noted that for metacarpophalangeal implants it has been observed a higher risk of intraoperative periprosthetic fractures when using cementation than implants which are inserted in a non-cemented manner [64].…”
mentioning
confidence: 99%
“…Periprosthetic fracture, observed with our second patient, can be a concern. Occurrence has been reported in approximately 2% of all TWAs independently of its intra-or postoperative occurrence observed at an average of 7.9 years after TWA, and for intraoperative occurrence only age was found to be a risk factor [61]. Non-displaced fractures can be treated by splinting, however, in order to achieve early stability for movement of the wrist, cementation and/or internal fixation are the methods of choice [62,63].…”
Section: Discussionmentioning
confidence: 99%